(untitled) (UNED Research Journal, 2017)
Innovative evaluation strategies are necessary in distance education systems, specially in higher levels, in which students are more critical and demanding. The objective of this study was to determine how an innovative evaluative strategy influenced students’ motivation and performance in a pilot course (Distance State University, Costa Rica). For this I applied a survey to the 14 students -aged 22 to 45 years- who took the course from 2014 to 2016. Students were highly satisfied with this innovative strategy, since it challenged them into being better professionals, which coincide with similar studies. In 2 practices, out of 4, performance was higher in 2016 than in 2014 and 2015, years where the innovation was not implemented. To improve performance and motivation, I recommend using this strategy in other courses that have practice in pilot plants, and to create a culture in which students receive a more formative evaluation.